Le Musée du Barreau de Paris, histoire et avenir - Basile Ader; Cindy Geraci (Criminocorpus)
There is currently no museum relating to the legal profession in France, nor is there a Museum of Justice. The Musée du Barreau, which belongs to the Ordre des Avocats à la Cour d'appel de Paris, is a unique institution in this respect. Its mission is to transmit and promote the history of lawyers. Heirs to the lawyers of the Paris Parliament, the Parisian lawyers have built up a significant heritage, consisting of books, works of art, paintings, sculptures, engravings, medals, manuscripts, etc., enriched over the centuries. Its private collections, comprising more than 12,000 works and books, concern the history of lawyers, but more generally that of Justice. Here is an overview of the Paris Bar Museum, from its origins to the present day.